The Result of the Declaration in the sense of Metaphor For Abd al-Rahman ibn Mustafa al-Aidarous (d. 1192 AH): An Investigation and Reference (Islamic Sciences Journal, 2023)
The nature of research and investigation required that the researcher presents to the reader something about the author’s life and writings in a preface that preceded the verified text. So the researcher had  dealt with the text as is well-known among the investigators, and had explained this in a special paragraph in (The Investigation Method).